ACADEMIC STRESS AND STRESS-COPING STRATEGY OF A HIGHER BATCH STUDENT WHO IS CONDUCTING THESIS - Rianti, Rachmi Dwi; Ikhsanudin, Ikhsanudin; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractEverybody experiences stress at one point or another in their lives, just at different levels and for different reasons. It is inevitable. And, writing a thesis is one of the most stressful moments in a student life, especially when the student is in the last semester before being dropped out. As XY's case in this present study. This study aimed to investigate what were the stressors that she encountered that made her late in finishing her thesis and how she coped with the situation. The researcher used case study as the method and observation, semi-structured interview, Gadzella?s SII Questionnaire, and Lazarus and Folkman?s Ways of Coping Questionnaire to gather the data. The result shows that the stressors that caused XY were family and personal problems, academic-related problem, and other minor problems such as the lack of material sources and finance. She coped with her stress in the ways of distancing, detaching, distracting herself from the stress sources, confining her problems to her close-ones and keeping her motivation high.Keywords: Academic Stress, Academic Stressors, Higher Batch Student, Stress-Coping Strategy